Evolving 4G KPIs to improve end user QoE for 4G LTE broadband systems. - Maposa, Darlington (Midlands State University, 2017)
In the last half decade data traffic has surpassed voice traffic in telecommunications networks. Legacy networks could not cope with the overwhelming data traffic and exponential increase in subscribers. To address legacy systems limitations in this regard 4G LTE was introduced. With reduced network elements and advanced robust modulation technologies 4th generation systems offer data speeds much more than 3G and wired networks. In addition, 4G offers a variety of services which could not be offered by earlier systems. Challenges in 4th generation systems arise from managing the complexity in user requirements that accompanies increase in subscribers. For legacy networks performance requirements was defined from operator perspective, gauging it against some performance metrics thresholds. But with so much services on offer from content providers service quality definition has also included user perspective. This thesis provides a detailed technical analysis of 4th generation systems and associated KPIs, users’ perception of quality requirements and how best these user QoE requirements can be combined with traditional KIPs to come with performance metrics that are used centric rather than operator centric.